Intratumoral genomic heterogeneity in advanced head and neck cancer detected by comparative genomic hybridization - Götte, Karl; Tremmel, Susanne Carina; Popp, Susanne; Weber, Susanne; Hörmann, Karl; Bartram, Claus R.; Jauch, Anna (Current research in head and neck cancer, 2005)
Objectives: Little is known about the extent of intratumoral genetic heterogeneity in head and neck squamous cell carcinoma (HNSCC). Material: Therefore, we examined 79 stage III and IV primary HNSCCs and matched lymph node metastases for over- and underrepresentation of specific chromosome regions by comparative genomic hybridization. Results: The overall ratio of gains and losses was higher in metastases (M) than in primary (P) tumors (4/1 vs. 2.5/1). Gains of 3q (78.1% P vs. 87.5% M) and 11q (78.1% P vs. 62.5% M), and deletions of 3p (43.8% P vs. 34.4% M) and 9p (31.3% P vs. 15.6% M) were most frequently detected. The highest rate of intratumoral discordance was observed for primary tumors and corresponding metastases (32.8%) compared to matched pairs of 2 metastases (26.5%), and of 2 anatomically distinct sides of 1 primary tumor (24.3%). Furthermore, the discordance rate was dependent on the primary tumor site (oral cavity 49.2%, oropharynx 31%, hypopharynx 30.3% and larynx 27.3%). In some tumors, the extent of genomic discordance argues against a monoclonal origin. Conclusion: We demonstrate a high individual variation of intratumoral genomic heterogeneity depending on the localization and selection of matched pairs. These findings are of specific importance in view of establishing prognostic markers.